Impact of COVID-19 on the Healthcare of Patients With Inflammatory Bowel Disease: A Comparison Between Epicenter vs. Non-epicenter Areas - Qiu, Yun; Zhang, Ying-Fan; Zhu, Liang-Ru; He, Jin-Shen; Tan, Jin-Yu; Tan, Nian-Di; Lin, Si-Nan; Lin, Xiao-Qing; Ghosh, Subrata; Chen, Min-Hu; Mao, Ren (Frontiers in Medicine, 2020)
Background and Aims: The COVID-19 pandemic poses a great challenge to healthcare. We aimed to investigate the impact of COVID-19 on the healthcare of patients with inflammatory bowel disease (IBD) in epicenter and non-epicenter areas. Methods: Patients with IBD from Hubei province (the epicenter of COVID-19) and Guangdong province (a non-epicenter area), China were surveyed during the pandemic. The questionnaire included change of medications (steroids, immunomodulators, and biologics), procedures (lab tests, endoscopy, and elective surgery), and healthcare mode (standard healthcare vs. telemedicine) during 1 month before and after the outbreak of COVID-19. Results: In total, 324 IBD patients from Guangdong province (non-epicenter) and 149 from Hubei province (epicenter) completed the questionnaire with comparable demographic characteristics. Compared to patients in Guangdong province (non-epicenter), significantly more patients in Hubei (epicenter) had delayed lab tests/endoscopy procedures [61.1% (91/149) vs. 25.3% (82/324), p < 0.001], drug withdrawal [28.6% (43/149) vs. 9.3% (30/324), p < 0.001], delayed biologics infusions [60.4% (90/149) vs. 19.1% (62/324), p < 0.001], and postponed elective surgery [16.1% (24/149) vs. 3.7% (12/324), p < 0.001]. There was an increased use of telemedicine after the outbreak compared to before the outbreak in Hubei province [38.9% (58/149) vs. 15.4% (23/149), p < 0.001], while such a significant increase was not observed in Guangdong province [21.9% (71/324) vs. 18.8% (61/324), p = 0.38]. Approximately two-thirds of IBD patients from both sites agreed that telemedicine should be increasingly used in future medical care. Conclusions: Our patient-based survey study in a real-world setting showed that COVID-19 resulted in a great impact on the healthcare of patients with IBD, and such an impact was more obvious in the epicenter compared to the non-epicenter area of COVID-19. Telemedicine offers a good solution to counteract the challenges in an unprecedented situation such as COVID-19.